Quantitative finance for physicists : an introduction - Schmidt, Anatoly B. (Amsterdam ; Boston : Elsevier Academic Press, 2005)
Presents an introduction to the fundamental and advanced finance principles and methods. This work helps readers to learn about key topics in quantitative finance such as option pricing, portfolio management and risk measurement.
Includes bibliographical references and index.
oif 20/08/15
Loan
Keywords: Finance -- Mathematical models